Построение программы развития сотрудника на основе процедуры оценки персонала - Ippolitova A. V. (Innovative technologies in science and education, 2016)
The article investigates the importance of personal and professional development of preschool educaters, as well as developing methods of development personnel course.
Keywords: педагог дошкольного образования; инструментарий оценки; развитие потенциала; assessment toolkit; сapacity development; preschool level educators